KESETIAAN, KEPERCAYAAN, NILAI, IDENTIFIKASI SOSIAL - Lerbin R Aritonang (Jurnal Manajemen., 2007)
This paper develops a framework for understanding the behaviors and practices of service providers that build or deplete consumer trust and themechanisms that convert consumer trust into value and loyalty in relational exchanges. The proposed framework uses a multidimensional conceptualization for the trustworthiness construct, incorporates two distinct facets of consumer trust, namely, frontline employees and management policies and practices, and specifies value as a key mediator of the trust-loyalty relationship. The proposed model is tested using data from service contexts - university (N = 327). The results support a tripartite view of trustworthiness evaluations along operational competence,operational benevolence, and problem-solving orientation dimensions. Moreover, the paper finds evidence of relationships between social identificatin and consumer loyalty.